Evaluation of West Sulawesi Provincial Sports Achievement Coaching After National Sports Week XX - Andi Dwi Sasmianto Rm.B; Hermawan Pamot Raharjo; Donny Wira Yudha Kusuma (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The problem in this study is the lack of sports achievements in the national arena, three PON events behind West Sulawesi have always been the key players in obtaining medals. This study aims to 1) evaluate the human resources of coaches and athletes after PON XX, 2) evaluate sports coaching programs, 3) evaluate sports infrastructure as a support for achievement coaching, 4) evaluate the allocation of funding for sports achievement coaching in West Sulawesi after PON XX.5) evaluate the management of KONI South Sulawesi in its function as a sports achievement coaching institution. This study uses a descriptive qualitative approach with a countenance evaluation model from Robert E. Stake, with antecedent, transaction and outcome stages. The subjects in the study were the KONI Management of West Sulawesi Province, coaches, athletes and the West Sulawesi Youth and Sports Office. Through observation, interview and documentation approaches, data validity using Triangulation, data analysis models used in research are data collection, data reduction, data presentation and conclusions. The results of the evaluation research on West Sulawesi sports achievement coaching after PON XX include: 1) the human resources of coaches and athletes in the process of coaching West Sulawesi sports achievements after PON XX in the medium category, 2) the West Sulawesi sports achievement coaching program after PON XX in the medium category, 3) infrastructure facilities in the process of coaching West Sulawesi sports achievements after PON XX are still not good, 4) funding during the post-PON XX training centering process is still not good, 5) related administrators in coaching sports achievements in West Sulawesi after PON XX are in the medium category.Conclusion: Sports achievement development in West Sulawesi has not run well after PON Papua XX, as for the suggestions that researchers can give, namely the West Sulawesi Provincial Government pays more attention to improving infrastructure and funding facilities, for the West Sulawesi Provincial KONI management should pay more attention directly to the obstacles when coaching achievements in each sport.